2012
DOI: 10.1007/s11116-012-9439-0
|View full text |Cite
|
Sign up to set email alerts
|

A complex network approach to understand commercial vehicle movement

Abstract: We introduce complex network analysis and use a commercial vehicle's observed trip as a proxy for a business relation between two facilities in its activity chain. We extract facility locations by applying density-based clustering to GPS data of commercial vehicle activities. The network among the facilities is then extracted by analysing the activity chains of more than 25 000 commercial vehicles. Centrality metrics proves useful and novel in identifying and locating key logistics players. Transport planners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…For example, Liu et al [29] used taxi trip data to explore the clustering characteristics of a person's travel activities within a city and found that some clusters showed that the boundary scope of some clusters was not consistent with the administrative boundaries. Similar studies have been conducted by Joubert et al [30], Zhong et al [31], etc.…”
Section: Introductionsupporting
confidence: 83%
“…For example, Liu et al [29] used taxi trip data to explore the clustering characteristics of a person's travel activities within a city and found that some clusters showed that the boundary scope of some clusters was not consistent with the administrative boundaries. Similar studies have been conducted by Joubert et al [30], Zhong et al [31], etc.…”
Section: Introductionsupporting
confidence: 83%
“…and means of transportation are a medium of interaction and communication between places, which ensures the continuity of economic, social and cultural life (Mouratidis et al, 2021;PEREIRA, 2014). The more vehicles that are used as a means of moving, the infrastructure needed must also be more adequate (Joubert & Axhausen, 2013;Pratiwi, 2020). The addition of volume and traffic generation pull is one of the causes of the decline in road performance (Saprykin et al, 2020;Setijadji, 2006).…”
Section: Infrastructurementioning
confidence: 99%
“…However, we found that very few studies explicitly consider the impact of urban transport vulnerability on the movement of freight using a complex network approach. The underrepresentation of freight systems in transport planning in general is a recognised fact (Joubert and Axhausen, 2013) and the situation is no different in network vulnerability studies. Darayi et al (2017) weighted a multi-modal freight transport network with commodity flows calculated by a typical four-step model.…”
Section: Transportation Applicationsmentioning
confidence: 99%
“…It also used gravity modelling as a proxy for freight movement instead of actual freight activity. Joubert and Axhausen (2013) were the first to explicitly address freight movement using complex networks. The authors constructed a network from real-life commercial vehicle activity chains, illustrating how centrality measures can be used to identify key logistics facilities in Gauteng, South Africa.…”
Section: Transportation Applicationsmentioning
confidence: 99%